THE ROLE OF PHOSPHATES AND NONIONIC SURFACTANTS IN ENHANCING THE DETERGENT PERFORMANCE OF SYNTHETIC DETERGENTS - Vakhobova Dinora Nigmatjon qizi; Erkaeva Nazokat Aktamovna; Tursunova Dildora Abdusattorovna; Erkayev Aktam Ulashevich (Modern American Journals, 2025)
The article examines the role of phosphates and nonionic surfactants in improving the washing performance of synthetic detergents. The provided data highlight the impact of phosphate additives on water softening, enhanced dispersing capacity of solutions, and stabilization of complex compounds with hardness ions. The contribution of nonionic surfactants in increasing the efficiency of removing contaminants of various origins, foam stabilization, and regulation of rheological properties of detergent compositions is considered. An analysis of their combined action in multicomponent detergent formulations demonstrates a synergistic effect, ensuring a significant increase in cleaning efficiency compared to the use of these components separately. The research results may be applied in the development of environmentally oriented, highly effective formulations of detergents for technical and household applications.
Keywords: Phosphates, nonionic surfactants, synthetic detergents, washing efficiency, complexation, foaming, water hardness, contaminant dispersion, chemical-technological properties, functional additives.